Círculos Operários no Ceará: “Instruindo, educando, orientando, moralizando” (1915-1963) - Santos, Jovelina Silva (2004)
The study accosts the Circle of Workmen in Ceará in the period that comprehends the foundation of the Circle of Christian Workman and Labourers of Fortaleza in 1915 and he First Regional Congress North and Northeast of the Workmen’s Circle in the year of 1963. The 1st part analyses the circle’s organization as a theological-politic project and as an instrument of the Catholic Church for her insertion in the world of work. It still makes a brief dialogue with the historiography of the circles in different spaces. The second part analyses the circle’s organization in Ceará, seeking to understand the estabilized relation with the sindicates and other organization. In the third part the focus is for education project of the workmen’s Circle comprehended in the dimension of a job turned toward the instruction and doctrination of the cearense workers in their diverse spaces. The fourth part visualizes over the cearense circles press like an informative and formative instrument, observing doctrinary function of this press.